Consensus revisited: quantifying scientific agreement on climate change and climate expertise among Earth scientists 10 years later. (20th October 2021) - Myers, Krista F; Doran, Peter T; Cook, John; Kotcher, John E; Myers, Teresa A
Abstract: The scientific consensus on human-caused global warming has been a topic of intense interest in recent decades. This is in part due to the important role of public perception of expert consensus, which has downstream impacts on public opinion and support for mitigation policies. Numerous studies, using diverse methodologies and measures of climate expertise, have quantified the scientific consensus, finding between 90% and 100% agreement on human-caused global warming with multiple studies converging on 97% agreement. This study revisits the consensus among geoscientists ten years after an initial survey of experts, while exploring different ways to define expertise and the level of agreement among these groups. We sent 10 929 invitations to participate in our survey to a verified email list of geosciences faculty at reporting academic and research institutions and received 2780 responses. In addition to analyzing the raw survey results, we independently quantify how many publications self-identified climate experts published in the field of climate change research and compare that to their survey response on questions about climate change. As well as a binary approach classifying someone as 'expert' or 'non-expert', we also look at expertise as a scale. We find that agreement on anthropogenic global warming is high (91% to 100%) and generally increases with expertise. Out of a group of 153 independently confirmed climate experts, 98.7% of those scientists indicated that the Earth is getting warmer mostly because of human activity such as burning fossil fuels. Among those with the highest level of expertise (independently confirmed climate experts who each published 20+ peer reviewed papers on climate change between 2015 and 2019) there was 100% agreement that the Earth is warming mostly because of human activity.